Validación de un instrumento para la medición de la sostenibilidad empresarial en pequeñas y medianas empresas - Osorio Atehortúa, Ubeimar Aurelio (Universidad Católica Luis Amigó, 2022)
This book presents the results of the research "Sustainability in MyPymes, an evaluation model at Latin American level", funded by the Luis Amigó Catholic University and the company Etipyme S.A.S., whose development allowed to design an initial diagnostic instrument of sustainability from the particularity of each organization, giving useful information that facilitates decision making in relation to the environmental, social and economic.